Methanol oxidation on PtRu/C electrocatalysts prepared by a microemulsion method - Godoi, Denis R.M. [UNESP]; Perez, Joelma [UNESP]; Villullas, H. Mercedes [UNESP] (The Electrochemical Society, 2007)
PtRu/C nanocatalysts were prepared by a microemulsion method using different values of water/surfactant molar ratio in order to get different particle sizes. Crystallite sizes and structural properties were determined by X-ray diffraction. Particle size and distribution were characterized by transmission electron microscopy and average composition was determined by energy dispersive X-ray analysis. Differential scanning calorimetry measurements indicated the presence of oxides in the as-prepared catalysts. The general electrochemical behavior was evaluated by cyclic voltammetry in 0.5 M sulfuric acid and the electrocatalytic activity towards the oxidation of methanol was studied in 0.5 M methanol acid solutions by potential sweeps and chronoamperometry. copyright The Electrochemical Society.
Keywords: (p ,p ,t) measurements; (PL) properties; Acid solutions; Average composition; Electrocatalytic activity (ECA); Electrochemical behaviors; Electrochemical Society (ECS); Energy dispersive X ray analysis (EDAX); General (CO); In order; methanol oxidation; Microemulsion methods; molar ratios; Nano-catalysts; PtRu/C electrocatalysts; Scanning calorimetry; X ray diffraction (XRD); Bioelectric phenomena; Blood vessel prostheses; Catalysis; Chemical analysis; Chemical modification; Chemical oxygen demand; Chemistry; Chronoamperometry; Cyclic voltammetry; Differential scanning calorimetry; Electrocatalysis; Electrocatalysts; Electrochemical oxidation; Electrochemistry; Electrolysis; Electron microscopes; Electron microscopy; Electron optics; Grain size and shape; Imaging techniques; Methanol; Microemulsions; Microscopic examination; Oxidation; Particle size; Particle size analysis; Scanning; Size distribution; Steel analysis; Structural properties; Sulfuric acid; Transmission electron microscopy; Voltammetry; X ray diffraction analysis; X rays; X ray analysis